Designing a knowledge management system with big data for data and information center of the Indonesian Ministry of health on software development - Setiawan, Alliefiandini; Wang, Gunawan (Gema Wiralodra, 2023)
Every company has essential information. This information can become company knowledge. Knowledge must be organized so that learning is often used optimally. If knowledge is optimally organized, people who want to use it will find it difficult to find it. Therefore, knowledge management is needed. Knowledge management is used everywhere. In this case, knowledge management will be used for application development. This knowledge was previously processed using ETL, where data would be collected, filtered, and combined with various sources. This knowledge management will be integrated with big data in the software development process so that users can easily find the necessary knowledge.